Effectiveness of modern insecticides in protection of apple planting from red-headed aphides - Yanovskyi, Y.; Suchanov, S.; Krykunov, I.; FomenkoА. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2020)
Goal. To investigate an efficacy of the insecticides Movento 100 SC (spirotetramate, 100 g/l), Sivanto Prime 200 SL (flupiradifuran, 200 g/l) and Transform WG (sulfoxaflor, 500 g/kg) on a reduction of a number and a harmfulness of red-headed or gray apple aphid (Disaphis devecta Walk.) in commercial apple orchards. Methods. A field method, in the commercial apple orchards under the conditions of educational production department of university. A type of apple trees was Golden Delicious. Planting scheme — 4.0 × 3.0 m. Year of planting — 1992. Crown shape — sparsely (improved) — tiered. Rootstock — MM-106. Phases of plant development at application timing — «after blooming, fruit size — up to 20 mm» (BBCH 72). Soil — shallow, low — humus dusty — loamy podzolic leached black soils: humus content — 1.3—2.5%; pH 4.8—5.2; mobile compounds Р2О5 — 130—180 mg/ kg and К2О — 8,9—9,2 mg/kg (by Chirikov method). The measures for care of the experimental site — loosening a soil in the stem strips during the growing period, an application of organic and mineral fertilizers, a pruning, a splaying of grass between the rows (row spacing),a protection from pests and diseases. The technical effectiveness of applications was determined in different rates against red-headed aphids in the apple orchards. Calculations were made according to generally accepted methods in plant protection and entomology. Results. The use of insecticides Movento 100 SC, Sivanto Prime 200 SL and Transform WG against red-headed aphids provided a reduction of this species in the number of 92.8—97.2%. It allowed to obtain a high — grade apple product with a yield of 1.7—1.9 times higher comparing to control. The outcome of non-standard products did not exceed 4.9% compare to 24.9% in the control (water treatment). Conclusions. The use of insecticides Movento 100 SC, Sivanto Prime 200 SL, Transform WG can reduce effectively the harmfulness of red-headed aphids in apple orchards and control its number during the growing period. A limiting the number of a current sucking species in the apple orchard by using the studied applications provided a yield increase and a marketable quality of the obtained fruit products.